Temporal factors affecting somatosensory–auditory interactions in speech processing - Ito, Takayuki; Gracco, Vincent L.; Ostry, David J. (Frontiers in Psychology, 2014)
Speech perception is known to rely on both auditory and visual information. However, sound specific somatosensory input has been shown also to influence speech perceptual processing (Ito et al., 2009). In the present study we addressed further the relationship between somatosensory information and speech perceptual processing by addressing the hypothesis that the temporal relationship between orofacial movement and sound processing contributes to somatosensory-auditory interaction in speech perception. We examined the changes in event-related potentials in response to multisensory synchronous (simultaneous) and asynchronous (90 ms lag and lead) somatosensory and auditory stimulation compared to individual unisensory auditory and somatosensory stimulation alone. We used a robotic device to apply facial skin somatosensory deformations that were similar in timing and duration to those experienced in speech production. Following synchronous multisensory stimulation the amplitude of the event-related potential was reliably different from the two unisensory potentials. More importantly, the magnitude of the event-related potential difference varied as a function of the relative timing of the somatosensory-auditory stimulation. Event-related activity change due to stimulus timing was seen between 160-220 ms following somatosensory onset, mostly around the parietal area. The results demonstrate a dynamic modulation of somatosensory-auditory convergence and suggest the contribution of somatosensory information for speech processing process is dependent on the specific temporal order of sensory inputs in speech production.